The integration of Character Education Inquiry Lesson Study in Learning Biology Scientific Attitudes to Improve Cognitive and Learning Outcomes Student Class VII SMPN I Singosari - Elly Lailatul Budur (Jurnal Pendidikan Sains, 2013)
Integrasi Pendidikan Karakter Melalui Inkuiri dengan Lesson Study dalam Pembelajaran Biologi untuk Meningkatkan Sikap Ilmiah dan Hasil Belajar Kognitif Siswa Kelas VII SMPN I Singosari Abstract: inquiry learning allows students to be involved actively think and find the sense he wanted to know. The knowledge and skills acquired students are expected not result in view of the facts, but the result of his own invention. Results of initial observations showed that students in SMP Negeri 1 Singosari still tend to memorize the lessons that lack process skills. Characters such students in the national education goals are also still far from the desired study was conducted to improve the scientific attitude and cognitive student learning outcomes through the integration of character education with guided inquiry method and lesson study seventh grade students of SMP Negeri 1 Singosari Type of research is research with a model Lesson Study using qualitative descriptive design. The results showed that an increase in their respective scientific attitude. Percentage completeness cognitive learning outcomes of students also increased. Thus it is suggested that teachers can implement inquiry learning as one variation of learning methods adapted to the material to be delivered. Additionally lesson study should be implemented effectively and the school culture. Key Words: character education, inquiry, lesson study, scientific attitudes, cognitive learning outcomes Abstrak: Pembelajaran inkuiri memungkinkan siswa dilibatkan secara aktif berpikir dan menemukan pengertian yang ingin diketahuinya. Pengetahuan dan keterampilan yang diperoleh siswa diharapkan bukan hasil mengingat fakta-fakta, tetapi hasil dari penemuan sendiri. Hasil pengamatan awal menunjukkan bahwa siswa  di SMP Negeri 1 Singosari masih cenderung menghafal pelajaran sehingga kurang memiliki keterampilan proses. Karakter siswa seperti dalam tujuan pendidikan nasional juga masih jauh dari harapan yang diinginkan Penelitian dilakukan untuk meningkatkan sikap ilmiah dan hasil belajar kognitif siswa melalui integrasi pendidikan karakter dengan metode inkuiri terbimbing dan lesson study siswa kelas VII SMP Negeri 1 Singosari. Jenis Penelitian adalah penelitian dengan model Lesson Study menggunakan rancangan deskriptif kualitatif. Hasil penelitian menunjukkan bahwa terjadi peningkatan pada masing-masing sikap ilmiah. Persentase ketuntasan hasil belajar kognitif siswa juga terjadi peningkatan. Dengan demikian disarankan agar guru dapat menerapkan pembelajaran inkuiri sebagai salah satu variasi metode pembelajaran yang disesuaikan dengan materi yang akan disampaikan. Selain itu lesson study perlu diterapkan secara efektif dan menjadi budaya sekolah. Kata kunci: pendidikan karakter, inkuiri, lesson study, sikap ilmiah, hasil belajar kognitif